Continuous stiffness monitoring of cemented sand through resonant frequency - Azenha, Miguel (2011)
Mixture formulation and in-situ quality control of the stabilized soils often represent difficult and challenging tasks. The present paper addresses the possibility of using a variant to a recently developed non-destructive technique for continuous monitoring of stiffness of hardening materials as a supporting means to the above-mentioned tasks. The material to be tested is placed inside a polycarbonate mold placed in simply supported conditions. The technique is based on the continuous monitoring of the first resonant frequency of this composite beam, which evolves as a consequence of the hardening of the material, and can be correlated with its E-modulus. The usefulness and potential of this experimental methodology for mixture formulation and quality control of stabilized soils is shown through a series of tests conducted on laboratory since the instant of mixing until 7 days. The conducted tests include complementary methodologies of characterization such as E-modulus measured on specimens with strain instrumentation, as well as monitoring with recourse to bender-extender elements.